Gastroesophageal reflux symptoms in infants in a rural population: longitudinal data over the first six months - Storms Michelle R; Van Howe Robert S (BMC, 2010)
Abstract Background Increasing numbers of infants are receiving prescription medications for symptoms associated with gastroesophageal reflux. Our aim was to prospectively measure reported gastroesophageal reflux symptoms in healthy term infants for the first six months of life. Methods In a prospective cohort study in the rural Upper Peninsula of Michigan, 128 consecutive maternal-infant pairs were followed for six months and administered the Infant Gastroesophageal Reflux Questionnaire Revised (I-GERQ-R) at the one-month, two-month, four-month, and six-month well-child visits. Results The I-GERQ-R scores decreased with age. Average scores were 11.74 (SE = 5.97) at one-month, 9.97(4.92) at two-months, 8.44(4.39) at four-months, and 6.97(4.05) at six months. Symptoms associated with colic were greatest at one month of age. Conclusion Symptoms of gastroesophageal reflux as measured by the I-GERQ-R decrease with age in the first six months of life in otherwise healthy infants; however the I-GERQ-R may have difficulty differentiating gastroesophageal reflux disease from colic in those under 3 months of age.